Dynamic analysis of laterally loaded single piles in sandy soils considering sliding and debonding on the pile-soil interface. (1st December 2020) - Ding, Zhaowei; Song, Chunyu; Chen, Longzhu; Shi, Kunpeng
Abstract: This paper proposes an analytical solution for the dynamic analysis of laterally loaded single piles in sandy soils that considers the effects of sliding and debonding on the pile-soil interface. These effects have received little attention in earlier studies and usually lead to an overestimate of the dynamic impedances of piles and soil. In this paper, the pile-soil interface is decomposed into three components, the bonding, sliding and debonding components, and the spread of the bonding and sliding areas is associated with the inertial friction angle of the soil around the pile. The effects of sliding and debonding of the pile-soil interface are investigated by using the radiant stress theory and the convolution method of Fourier coefficients. The displacement fields and attenuation functions of the soil are then derived by the potential functions. The dynamic impedances of the pile top are calculated by the Adomian decomposition method. The results are presented by contours in both the horizontal and vertical planes, and the present solution is validated through comparisons against a finite element simulation and other analytical solutions. The influences of related parameters, including the load frequency, effective inertial friction angle of the soil, modulus ratio between the pile and soil and pile slenderness ratio, have also been studied in this paper. Highlights: A continuum solution for dynamic analysis of laterally loaded piles in sandy soils is proposed. The pile-soil interface is decomposed to three components: bonding, sliding, and debonding. The spreads of bonding and sliding areas are associated with the inertial friction angle of soil around pile. The effects of sliding and debonding are investigated through the displacement fields and attenuation functions.